An unusual presentation of a dural arteriovenous fistula of the sphenoparietal sinus. (14th March 2014) - Macdonald, Andrew; Plaha, Puneet; Byrne, James
Abstract : Dural arteriovenous fistulae (DAVFs) are a rare form of intracranial arteriovenous malformation. We present the case of a patient who presented in a previously undescribed manner with facial swelling and bruising initially misdiagnosed as cellulitis. He was found subsequently to have DAVFs of the sphenoparietal sinus that had hemorrhaged. The rarity of DAVFs at this location may account for this unique presentation. Successful treatment was achieved by transarterial embolization.